Duration of cooling with water for thermal burns as a first aid intervention: A systematic review. Issue 2 (March 2022) - Djärv, Therese; Douma, Matthew; Palmieri, Tina; Meyran, Daniel; Berry, David; Kloeck, David; Bendall, Jason; Morrison, Laurie J.; Singletary, Eunice M.; Zideman, David; ,; ,
Highlights: From 560 screened references, we included 4 studies. Out of 5978 patients, 2893 (48%) reported a cooling duration of ≥20 min IWe found no association between duration of cooling and size/depth of burn, days to re-epithelialization or skin grafting. Confidence in the estimate of effect, for the outcomes evaluated, was very low due to very serious risk of bias Abstract: Background: Cooling thermal burns with running water is a recommended first aid intervention. However, guidance on the ideal duration of cooling remains controversial and inconsistent across organisations. Aim: To perform a systematic review of the evidence for the question; Among adults and children with thermal burn, does active cooling using running water as an immediate first aid intervention for 20 min or more, compared with active cooling using running water for any other duration, change the outcomes of burn size, burn depth, pain, adverse outcome (hypothermia) or complications? Method: We searched Medline, Embase, Cochrane Database of Systematic Reviews and used ROBINS-I to assess for risk of bias. We used Grading of Recommendations, Assessment, Development and Evaluation methodology for determining the certainty of evidence. We included all studies that compared the selected outcomes of the duration of cooling of thermal burns with water in all patient ages. (PROSPERO registration number: CRD42021180665). From 560 screened references, we included four observational studies. In these studies, 48% of burns were cooled for 20 min or more. We found no benefit for a duration of 20 min or more of cooling when compared with less than 20 min of cooling for the outcomes of size and depth of burn, re-epithelialization, or skin grafting. The evidence is of very low certainty owing to limitations in study design, risk of bias and indirectness. Conclusion: The optimal duration of cooling for thermal burns remains unknown and future prospective research is indicated to better define this treatment recommendation.